2004
DOI: 10.1111/j.1600-6143.2004.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Renal Retransplantation after Post-Transplant Lymphoproliferative Disease

Abstract: Post-transplant lymphoproliferative disease (PTLD) is a rare but severe complication of renal transplantation. Reduction of immunosuppression is essential for controlling PTLD but may induce graft loss. Retransplantation after PTLD is considered dangerous, because immunosuppressive treatment resumption may trigger hematological relapse. We retrospectively report six patients (five adults, one child) who underwent a second renal transplantation after successfully treated PTLD.Epstein-Barr virus (EBV) serology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Six/six patients had their immunosuppression lowered and five/six underwent graft nephrectomy as part of PTLD treatment. Complete remission was achieved in all six patients at least two yr before consideration for kidney retransplantation . There were no cases of clinical recurrence after a median follow‐up of 30 months.…”
Section: Discussionmentioning
confidence: 81%
“…Six/six patients had their immunosuppression lowered and five/six underwent graft nephrectomy as part of PTLD treatment. Complete remission was achieved in all six patients at least two yr before consideration for kidney retransplantation . There were no cases of clinical recurrence after a median follow‐up of 30 months.…”
Section: Discussionmentioning
confidence: 81%
“…The few series looking at results of retransplantation after PTLD in a prior allograft did not report any recurrence of PTLD (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…However, a period of at the very least 1 year seems appropriate. A recent survey of French transplant centres (Karras et al , 2004) identified a series of six patients with PTLD, including four in whom the disease was confined to the kidney transplant. After successful treatment (which in all cases involved transplant nephrectomy) re‐transplantation was undertaken between 50 and 128 months after diagnosis of PTLD and 29–97 months (mean 46 months) after graft nephrectomy.…”
Section: Management Of Re‐transplantationmentioning
confidence: 99%